The oppression concept based on Soyinka's a Dance of the Forests - Malek Awfi Jassim (مجلة اداب ذي قار)
The concept of oppression is one of the most vital concepts in contemporary political discourses in the literary works. This concept has some interdisciplinary characteristics which are associated with culture, religion, sociology and politics. The present study speaks to the topics of oppression and protest in the post-colonialism era and shows how oppression reinforces the rational justification of the rebuttal of the British existence on lands of the colonized countries. It also discusses how the colonized people strive to   maintain their social, cultural and traditional characteristics despite the colonial existence on their homeland, as such, the colonial encounters between colonized countries and the British Empire was discussed to unravel the colonized people's will to be safe of the colonizers oppression. The study also shows how the core conceptual essence of rebellion and violence is the conspiratorial reaction against oppression and exploitation. This is because oppression and exploitation usually result in marginalization and deprivation. The colonized people begin to lose their sense of dignity and they thus strenuously try to obliterate the colonial hegemony and its oppressive entity. In this respect, rebellion and violence were apparent representations of the fictional resistance portrayed in the selected literary works of the present study. This   study further sheds light on the precise fabric of the colonial attitudes that emerged out of the British colonialism in the nineteenth century, it strives to offer a profound conceptualization of how the terrorism has spread all over the colonized countries lands   after such colonialism, it also shows how oppression plays an essential factor in conveying the real sense of terrorism through the literature. It also accentuates the ideological confrontation between colonized countries and the British Empire to explore the negative impact of the Western hegemony on the colonized minorities in those countries. The Western attitudes, exemplified in the British imperialism, resulted in hegemonic power that belittled the existence of influence of those colonized countries over their own homeland, which resulted in resistance to gain liberty and independence. This study explained the study's methodology through explaining the theoretical background of the concepts of oppression and protest that will be examined in the research. The methodological chapter first introduced post-colonialism as a critical theory. Then, it discussed Fanon's concept of oppression. The methodological   application of these concepts was clarified in a conceptual diagram to describe their interpretation of the selected play.